Tiddler - Donaldson, Julia; Scheffler, Axel (London : Alison Green Books, 2007)
Tiddler the fish is always getting into trouble for telling tall stories until one day he is actually caught in a fisherman's net and taken far away from home.
K-3.
K-3
Text in traditional Chinese.
Keywords: Fishes -- Juvenile fiction; Truthfulness and falsehood -- Juvenile fiction; Fishes -- Fiction; Truthfulness and falsehood -- Fiction; Fishes -- Fiction; Truthfulness and falsehood -- Fiction; Picture books for children